METHODS OF STUDYING THE LANGUAGE OF PRINT MEDIA IN THE SOCIOLINGUISTIC ASPECT - Israil, Mukaddas (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The purpose of the scientific article is to study the sociolinguistic aspect of the printed media text and its impact on society, to study the scientific and theoretical views of philologists, as well as to make suggestions. Theoretical, comparative, classification and descriptive methods were used to cover the topic of the scientific article. The sociolinguistic approach to the study of media texts helps to understand the interaction of language and social factors in mass communication.